A phosphorylation-deficient mutant of Sik3, a homolog of Sleepy, alters circadian sleep regulation by PDF neurons in Drosophila - Kobayashi, Riho; Nakane, Shin; Tomita, Jun; Funato, Hiromasa; Yanagisawa, Masashi; Kume, Kazuhiko (Frontiers in Neuroscience, 2023)
Sleep behavior has been observed from non-vertebrates to humans. Sleepy mutation in mice resulted in a notable increase in sleep and was identified as an exon-skipping mutation of the salt-inducible kinase 3 (Sik3) gene, conserved among animals. The skipped exon includes a serine residue that is phosphorylated by protein kinase A. Overexpression of a mutant gene with the conversion of this serine into alanine (Sik3-SA) increased sleep in both mice and the fruit fly Drosophila melanogaster. However, the mechanism by which Sik3-SA increases sleep remains unclear. Here, we found that Sik3-SA overexpression in all neurons increased sleep under both light–dark (LD) conditions and constant dark (DD) conditions in Drosophila. Additionally, overexpression of Sik3-SA only in PDF neurons, which are a cluster of clock neurons regulating the circadian rhythm, increased sleep during subjective daytime while decreasing the amplitude of circadian rhythm. Furthermore, suppressing Sik3-SA overexpression specifically in PDF neurons in flies overexpressing Sik3-SA in all neurons reversed the sleep increase during subjective daytime. These results indicate that Sik3-SA alters the circadian function of PDF neurons and leads to an increase in sleep during subjective daytime under constant dark conditions.